"My job is to deal with what I can": HIV care providers' perspectives on adherence to HAART, addictions, and comprehensive care delivery in Vancouver, British Columbia. Issue 5 (19th October 2016) - Orchard, Treena; Salters, Kate; Michelow, Warren; Lepik, Katherine; Palmer, Alexis; Hogg, Robert
Abstract: People with drug addictions have among the lowest rates of adherence to HIV medications (i.e. HAART) of any infected population, which is often explained through reference to the instability associated with problematic drug use and the 'chaos' that is assumed to characterize the lives of people with addictions. Many studies examine the links between addiction and adherence from the perspective of HIV-positive populations, but few explore how HIV care providers think about addictions, their impact on adherence, and how to incorporate the complex health needs of drug-using populations into comprehensive HIV care practices. Using qualitative data from a pilot study on adherence to HAART among people with drug addictions in Vancouver, British Columbia, this paper examines how eight HIV care providers (i.e. physicians, pharmacists, and community-based service providers) approach these interconnected issues. Our findings illustrate that while addictions often complicate adherence to HAART, this is not a universal reality, and the kinds of drugs used as well as the individual capacities of these patients also factor significantly in their adherence success. The organization of the HIV care environment, which is highly stratified and provides certain professionals with more resources and structural capabilities to deliver comprehensive care than others, also plays a large role in our participants' abilities to address the health needs of their clients with addictions. We recommend that the current HIV care delivery system be adapted to ensure more integrated care and greater equity across the different groups of providers working in the field of HIV care.